Mygalin: A New Anticonvulsant Polyamine in Acute Seizure Model and Neuroethological Schedule - Dornela Godoy, Lívea; Luiz Liberato, José; Ismael da Silva, Pedro; Ferreira dos Santos, Wagner (Central Nervous System Agents in Medicinal Chemistry, 2013)
Polyamines are compounds that interact with ionotropic receptors, mainly modulating the NMDA receptor, which is strictly related to many neurologic diseases such as epilepsy. Consequently, polyamines rise as potential neuropharmacological tools in the prospection of new therapeutic drugs. In this paper, we report on the biological activity of synthetic polyamine Mygalin, which was tested as an anticonvulsant in model of chemically induced seizures. Male Wistar rats were injected with vehicle, diazepam, MK-801 or Mygalin at different doses followed by Pentylenetetrazole or N-Methyl-D-Aspartate administration. Mygalin presented protection against seizures induced by both NMDA injections and PTZ administration by 83.3% and 16.6%, respectively. Moreover, it prolonged the onset of tonic-clonic seizures induced by PTZ. Furthermore, it was tested in neuroethological schedule evaluating possible side-effects and it presented mild changes in Open Field, Rotarod and Morris Water Maze tests when compared to available anticonvulsant drugs. The mechanism underlying the anticonvulsant effect of Mygalin is noteworthy of further investigation, nevertheless, based on these findings, we hypothesize that it may be wholly or in part due to a possible NMDA receptor antagonism. Altogether, the results demonstrate that Mygalin has an anticonvulsant activity that may be an important tool in the study of prospection of therapeutics in epilepsy neuropharmacology.
Keywords: Open Field